2007
DOI: 10.1603/0046-225x(2007)36[1073:dbftav]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Forest Type and Vertical Strata in the Diversity and Composition of Hymenpteran Families and Mymarid Genera in Northeastern Temperate Forests

Abstract: Most insects' assemblages differ with forest type and show vertical stratification. We tested for differences in richness, abundance and composition of hymenopteran families and mymarid genera between sugar maple (Acer saccharum) and white pine (Pinus strobus) stands and between canopy and understory in northeastern temperate forests in Canada. We used flight interception traps (modified malaise traps) suspended in the canopy and the understory in a split-split block design, with forest type as the main factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
7
37
0
2
Order By: Relevance
“…Los ejemplares colectados se separaron in situ del material abiótico y se fijaron en etanol al 70% para su preservación y posterior transporte al laboratorio, donde se realizó la separación y determinación taxonómica hasta nivel de familia empleando claves especializadas (Thorp & Covich, 2001;Merrit, Cummins & Berg, 2008;Krantz & Evans, 2009) con ayuda de un microscopio estereoscópico Zeiss modelo Stemi 1 000. La riqueza de táxones fue obtenida contando las familias por sitio y época, se modeló una curva de rarefacción basada en el número de muestras versus número acumulativo de familias de todo el periodo de estudio tal como se ha utilizado por Vance, Smith, Malcolm, Huber & Bellocq (2007), las curvas de rarefarección se generaron con el programa EstimateS 8.2.0 (Colwell, 2009), así también, se construyó la curva de acumulación de familias por muestra.…”
Section: Macroinvertebrados Acuáticosunclassified
“…Los ejemplares colectados se separaron in situ del material abiótico y se fijaron en etanol al 70% para su preservación y posterior transporte al laboratorio, donde se realizó la separación y determinación taxonómica hasta nivel de familia empleando claves especializadas (Thorp & Covich, 2001;Merrit, Cummins & Berg, 2008;Krantz & Evans, 2009) con ayuda de un microscopio estereoscópico Zeiss modelo Stemi 1 000. La riqueza de táxones fue obtenida contando las familias por sitio y época, se modeló una curva de rarefacción basada en el número de muestras versus número acumulativo de familias de todo el periodo de estudio tal como se ha utilizado por Vance, Smith, Malcolm, Huber & Bellocq (2007), las curvas de rarefarección se generaron con el programa EstimateS 8.2.0 (Colwell, 2009), así también, se construyó la curva de acumulación de familias por muestra.…”
Section: Macroinvertebrados Acuáticosunclassified
“…Therefore, we might expect the stratification of herbivores and associated parasitoids to exist in temperate forests. However, studies of parasitoid stratification are also scarce and are often limited to surveys of adults (e.g., Compton, Ellwood, Davis, & Welch, 2000; Pucci, 2008; Stireman et al., 2012; Vance, Smith, Malcolm, Huber, & Bellocq, 2007), restricting our understanding of trophic links. Consequently, knowledge of the stratification of parasitoids and parasitism rates along a vertical gradient in a temperate forest remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed in temperate forests also showed a vertical stratification in the community composition of hymenopterans (Vance et al 2007;Pucci 2008;Sobek et al 2009;Ulyshen et al 2010Ulyshen et al , 2011. Vance et al (2007) found that, in northeastern temperate forests in Canada, Spheciformes are more common in the canopy than in the understory, suggesting that highly mobile hymenopterans may spend significant amounts of time foraging in this habitat. A similar result was found by Sobek et al (2009), who collected more cavity-nesting bees -including Spheciformes -in the canopy of a broadleaf forest in Germany.…”
Section: Discussionmentioning
confidence: 85%
“…Forest managers have often ignored the effects that certain silvicultural practices would have on the diversity of insects associated with higher strata of the forest. In recent years, improved methods to access canopies gave the opportunity to sample insects of this habitat (Basset et al 1997(Basset et al , 2003Vance et al 2007), showing that canopies can host some rarely collected or undescribed species (Floren & Schmidl 1999Thunes et al 2004;Vance et al 2007;Di Giovanni et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation